Implementasi Metode Prototype Pada Sistem Informasi Penjualan Berbasis Web: Sistem Informasi, Penjualan, Web, UMKM, Prototype - Erniyanti Lawolo; Yani Prihati; Satrio Agung Prakoso (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In today's digital era, the use of technology has become a primary need in supporting business activities, including in the micro, small, and medium enterprise sector, MSMEs are required to be more digitally literate in order to compete and win the competition in the business world. MertaBeauty is an MSME engaged in the sale of cosmetic and skincare products, but still uses manual methods in managing sales, stock, and reports, which hinders operational efficiency in running its business has not maximized the use of digital which makes the transaction process slow and allows errors in recording. This study aims to build a web-based sales information system to simplify the transaction process, product management, and report preparation. The method used is prototyping, with the final result being a web-based system that supports the management of products, transactions, stock, promotions, and sales reports. The implementation of this system is expected to increase operational effectiveness, as well as support MertaBeauty's digital marketing strategy more optimally. The prototyping method is used because it is a flexible, efficient, and user-centered way to develop products. It helps ignite the fire, minimize risks, and produce products that are more in line with market and user needs.